Variasi Rajutan Bambu Petung Sebagai Pengganti Tulangan Baja Dari Kuat Lentur FS 4,7 MPA - Surya Sefgan; Farlin Rosyad (Sekolah Tinggi Teknik - PLN, 2019)
In this globalization era, almost all buildings use concrete with steel reinforcement as the main component of building frames. it is known that the basic material for steel is iron ore, and iron ore is a non-renewable natural resource, while its supply in nature is increasingly limited. Therefore, the price of steel reinforcement also increased. therefore, there needs to be an alternative replacement of steel reinforcement in concrete. Bamboo has a fairly high tensile strength, between 100-400 MPa, almost equal to the tensile strength of steel reinforcement equivalent to ½ to ¼ of the ultimate stress of steel reinforcement shows the same results and tensile strength of bamboo can reach 1280 kg / cm2. Bamboo is used as reinforcement in concrete with knitted shapes and patterns. In this research, the flexural strength test of 15 concrete blocks measuring 15 X 15 X 60 Cm was carried out when the concrete age was 28 days with 3 different variables. The results showed that bamboo reinforced concrete beams had an average maximum flexural strength value of 7.20 MPa. So that the use of petung bamboo reinforcement has a positive effect and deserves to be used as an alternative to steel reinforcement.